JENIS DAN PROSES PEMBENTUKAN ADJEKTIVA DALAM BAHASA MINANGKABAU DI KENAGARIAN SUNGAI ABANG KECAMATAN LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Rahman, Milna; Agustina, Agustina; Manaf, Ngusman Abdul (Jurnal Bahasa dan Sastra, 2018)
This study aimed to describe (1) type adjectives in Minangkabau language in kenagarian Sungai Abang subdistrict Lubuk Alung district Padang Pariaman, and (2) the process of forming adjective in Minangkabau language in kenagarian Sungai Abang subdistric Lubuk Alung district Padang Pariaman. This type of research is qualitative research with descriptive method. The method of data collection was using the method of referring and recording technique. Analyzing the data was done in the form of activities as follows: (1) describes the recording data into written language, (2) identify the data in accordance with the format provided, (3) classify the data into the type and process of the formation of the adjective, and (4) do data deduction based on research result. The data of this research are sentence containing the adjectives expressed by the community in kenagarian Sungai Abang subdistrict Lubuk Alung district Padang Pariaman. The source of this research is Minangkabau language especially oral language of society in kenagarian Sungai Abang subdistrict Lubuk Alung district Padang Pariaman. Based on the results of the research obtained the following results, first adjectives in Minangkabau language in kenagarian Sungai Abang subdistrict Lubuk Alung district Padang Pariaman is as follows: (1) characteristic adjective (character or temperament), (2) color adjectives, (3) shape adjectives, (4) size adjectives, (5) sensory adjectives, (6) time adjectives, (7) distance adjectives, (8) speed adjectives, (9) power adjunctive adjectives, (10) adjectiva adjectives. Secondly, there are two adjunctive adjunctive processes in the Minangkabau language, which are basic adjectives and derivate adjectives that can be sorted on beraffixed adjectives, duplicated adjectives and compounded adjective adjectives.Â Keywords: Adjectives, Word-forming, Minangkabau Language